Public expenditure review of social protection programs in the Philippines - Sicat, Charlotte Justine D.; Mariano, Maria Alma P. (Research Paper Series)
In a developing country such as the Philippines, social protection is crucial in providing support to the poor and vulnerable. There has been recent progress in the design and delivery of social protection programs, owing largely to a more coherent social protection strategy and framework introduced in 2009. Efforts to consolidate programs and improve their targeting, design, and implementation are well documented. In addition, social protection programs were believed to have contributed to an observed reduction in poverty and inequality. However, more work is needed to increase the coverage, as well as improve the implementation and coherence of social protection policy. This paper aims to provide an overall view of national government social protection expenditures in the Philippines. Public expenditure trends in social protection were examined, with emphasis on selected major programs. Social protection efforts in the Philippines were compared with those in other countries and a review of existing literature on current social protection programs in the country was made to guide policymakers in rethinking either the design or the existence of these programs. The paper concluded with recent developments in social protection policy that could be continued to further the gains of social protection efforts in the last decade.